Cytokine Interferon‐γ suppresses the function of capsule myofibroblasts and induces cell apoptosis. Issue 11 (23rd February 2017) - Mattyasovszky, Stefan G.; Mausbach, Stefan; Ritz, Ulrike; Wollstädter, Jochen; Schmidtmann, Irene; Baranowski, Andreas; Drees, Phillipp; Rommens, Pol M.; Hofmann, Alexander
ABSTRACT: Myofibroblasts (MFs), a contractile subset of fibroblasts, play a pivotal role in physiological wound healing and in the development of many fibroconnective disorders. The complex cytokine network regulating the function of MFs in joint stiffness is still poorly understood. In this in vitro study, we investigated the effect of the cytokine Interferon‐gamma (IFN‐γ) on MFs isolated from human joint capsules. MFs were cultivated either in the presence of increasing concentrations of IFN‐γ alone or in combination with IFN‐γ neutralizing antibodies. Cell viability, cytotoxicity, apoptosis, and mRNA gene expression of the MF markers alpha‐smooth muscle actin (α‐SMA) and collagen type I were analyzed in MF cultures. Contraction potential was analyzed in an established collagen gel contraction assay simulating the extracellular matrix. Using immunofluorescence staining, we could verify that MFs express IFN‐γ‐receptor (R)‐1 on their membrane. IFN‐γ decreased MF viability and significantly elevated the apoptosis rate in a dose‐dependent manner. IFN‐γ down‐regulated α‐SMA and collagen type I mRNA expression which was associated with a diminished MF mediated contraction of the gel matrices. These effects were suppressed by simultaneous treatment of cells with a neutralizing IFN‐γ antibody. Our experiments confirm the hypothesis that the cytokine IFN‐γ is a crucial component of the regulatory network of capsule MFs. IFN‐γ notably influences the ability of MFs to contract collagen matrices by suppressing α‐SMA gene expression. IFN‐γ is toxic for MFs in high concentrations and may negatively regulate the number of pro‐fibrotic MFs during the healing process via induction of cell apoptosis. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2524–2533, 2017.